Strategi promosi perpustakaan berbasis media sosial melalui pendekatan marketing mix 7p: systematic literature review tahun 2011–2024 - Rahma Nia Tasyianda; Ayu Widary; Anugrah Mulia Daulay; Mohd. Rafly (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2026)
Background of the Study: The development of digital technology and social media has encouraged libraries to adapt their promotional strategies to changing user information behavior. Previous studies, including Qurroti and Rofifah (2024), have examined social media use for library promotion, focusing on benefits, challenges, and platform utilization. However, limited attention has been given to how social media-based library promotion is implemented through the integrated perspective of the 7Ps marketing mix. As a result, existing studies provide limited insight into how marketing elements interact in supporting digital library promotion. Objectives:  This study aims to analyze the implementation of the 7Ps marketing mix in social media-based library promotion. Method: This study employed a Systematic Literature Review (SLR) of 23 articles published between 2011 and 2024 from Google Scholar, Garuda, DOAJ, and SINTA. The selected articles were screened using predefined criteria and analyzed through thematic synthesis based on the 7Ps framework. Finding:  Promotion and people emerged as the most dominant elements, while price and physical evidence received less attention. The findings indicate a shift toward user-centered promotion emphasizing engagement, digital communication, and service visibility. Conclusion: Conclusion: This study highlights the importance of integrating the 7Ps marketing mix to support effective library promotion in digital environments.